Survivors’ Experiences of Intimate Partner Violence and Shelter Utilization During COVID-19 - Ravi, Kristen E. (Journal of family violence, 2022)
This paper examines the effects of COVID-19 on service-engaged female survivors of IPV and makes recommendations for service providers based on these survivors’ voices. The researchers adopted an exploratory, descriptive, and qualitative approach to inquiry due to the novelty of the research questions during the early days of the COVID-19 in March 2020. Semi-structured interviews with service-engaged survivors were analyzed using inductive and deductive coding processes. Two categories arose from our qualitative questions. The first category, related to experiences with service providers, included the themes of varying levels of support and isolation. Within the theme of isolation, survivors discussed both positive and negative aspects of isolation. The second category refers to the impact of COVID-19 on survivors’ daily lives and focused on the theme of escalation. The theme of escalation had two subthemes 1) escalation of life-generated risks and 2) escalation of partner-generated risks. Given that the pandemic will continue until vaccines are fully distributed and that future public health emergencies may mirror many of the challenges identified in the current context, survivors residing at home will continue to need services, and agencies will continue to need additional resources to provide them. Therefore, we discuss recommendations that can have a bearing on services offered in the future.